Meta analysis of business valuation solutions – are AI based methods better? - Aljaž Herman; Damijan Mumel; Timotej Jagrič (Mednarodno Inovativno Poslovanje)
Purpose of the article – this article addresses the challenge of accurately assessing business value in today's dynamic environment, exploring the limitations of traditional valuation methods and the potential of modern, technology-driven approaches.